2020
DOI: 10.1103/physrevresearch.2.012066
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Cooper pairing away from the Fermi level and its spectroscopic signature in twisted bilayer graphene

Abstract: We investigate phonon-mediated Cooper pairing in flat electronic band systems by solving the full-bandwidth multiband Eliashberg equations for superconductivity in magic angle twisted bilayer graphene using a realistic tight-binding model. We find that Cooper pairing away from the Fermi level contributes decisively to superconductivity by enhancing the critical temperature and ensures a robust finite superfluid density. We show that this pairing yields particle-hole asymmetric superconducting domes in the temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
(89 reference statements)
1
18
0
Order By: Relevance
“…This system exhibits two flat bands close to the Fermi energy, as reported by both theory [17][18][19] and experiment [20][21][22][23][24]. These bands are gaped out from the remaining electron energies, and, together with a reasonably large phonon frequency [25,26] that has been shown to be relevant for explaining superconductivity [27], constitute an ideal testing ground for the phenomenon discovered here. Although the predicted intensity of the replica bands is relatively weak, we propose here their detection in TBG in the foreseeable future.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…This system exhibits two flat bands close to the Fermi energy, as reported by both theory [17][18][19] and experiment [20][21][22][23][24]. These bands are gaped out from the remaining electron energies, and, together with a reasonably large phonon frequency [25,26] that has been shown to be relevant for explaining superconductivity [27], constitute an ideal testing ground for the phenomenon discovered here. Although the predicted intensity of the replica bands is relatively weak, we propose here their detection in TBG in the foreseeable future.…”
supporting
confidence: 68%
“…For further details on the theory see also Refs. [12,27] and Appendix A. For sake of clarity, we note that the hereinvestigated phenomenon cannot be described within the Bardeen-Cooper-Schrieffer (BCS) model, which assumes a frequency-independent order parameter, absence of mass renomalization, and an electronic bandwidth W that is much larger than the phonon frequency, W ≫ Ω.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pairing interaction responsible for superconductivity in TBG has been intensively studied. Among other possible pairing mechanisms, the effect of phonons (12)(13)(14)(15)(16)(17)(18)(19) (see also ref. 20), the proximity of the chemical potential to a van Hove singularity in the density of states (DOS) (21)(22)(23)(24)(25) and excitations of insulating phases (26)(27)(28) (see also refs.…”
mentioning
confidence: 99%
“…Early studies identified that the presence of a flat-band could in fact give rise to a linear dependence of the transition temperature on the strength of the attractive interactions [46,47], generating hope of achieving high critical temperatures. With the discovery of superconductivity in magic-angle twisted-bilayer graphene [43], interest in flat-band superconductivity rocketed [48][49][50][51][52]. Recently, it has also been discovered that superconductivity in twisted trilayer graphene can survive in-plane magnetic fields beyond the Chandrasekhar-Clogston limit [53], which has been interpreted as an indication of spin-triplet pairing [53,54].…”
mentioning
confidence: 99%